EFFICACY OF INTRAVITREAL AFLIBERCEPT IN MACULAR TELANGIECTASIA TYPE 1 IS LINKED TO THE OCULAR ANGIOGENIC PROFILE. Issue 12 (December 2017) - Kowalczuk, Laura; Matet, Alexandre; Dirani, Ali; Daruich, Alejandra; Ambresin, Aude; Mantel, Irmela; Spaide, Richard F.; Turck, Natacha; Behar-Cohen, Francine
Abstract : Purpose: To evaluate intravitreal aflibercept in macular telangiectasia Type 1 (MacTel 1) patients and measure their ocular angiogenic profile. Methods: Eight subjects with MacTel 1 refractory to bevacizumab, ranibizumab, or laser therapy and switched to aflibercept were included. Best-corrected visual acuity, central macular thickness, and cystic areas quantified on optical coherence tomography B-scans were assessed during 12 months. Perifoveal capillary densities were measured on optical coherence tomography angiography. Aqueous humor was sampled from six patients and eight control subjects undergoing cataract extraction. Growth factors were quantified using a multiarray immunoassay. Results: Over 12 months, patients received 6.6 ± 1.4 (range, 5–8) intravitreal aflibercept injections. Twelve months after switching to aflibercept, best-corrected visual acuity increased by ≥5 letters in 5 of 8 patients, compared with preaflibercept levels. Mean best-corrected visual acuity improved from 79.6 (∼20/50) to 88.0 (∼20/35) Early Treatment Diabetic Retinopathy Study letters ( P = 0.042), and central macular thickness decreased from 434 ± 98 μ m to 293 ± 59 μ m ( P = 0.014). Compared with control subjects, the profile of angiogenic factors in MacTel 1 eyes revealed no difference in vascular endothelial growth factor-A levels but significantly higher levels of placental growth factor ( P = 0.029), soluble vascular endothelial growth factor receptor-1 (sFlt-1; P = 0.013), vascular endothelial growth factor-D ( P = 0.050), and Tie-2 ( P = 0.019). Placental growth factor levels inversely correlated with both superficial and deep capillary plexus densities on optical coherence tomography angiography ( P = 0.03). Conclusion: The clinical response to aflibercept coupled to the angiogenic profile of MacTel 1 eyes support the implication of the placental growth factor/Flt-1 pathway in MacTel 1. Abstract : Supplemental Digital Content is Available in the Text.In this interventional case series, 8 patients presenting macular telangiectasia Type 1 with macular edema were treated by intravitreal aflibercept. The favorable clinical response observed with this treatment is consistent with the profile of angiogenic factors analyzed in their aqueous humors.